2017
DOI: 10.1016/j.addbeh.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

“It's how we deal”: Perceptions of LGB peers' use of alcohol and other drugs to cope and sexual minority adults' own coping motivated substance use following the Pulse nightclub shooting

Abstract: Sexual minority stress experiences (e.g. prejudice, victimization, etc.) and peer substance use norms (e.g. peers’ frequency of use and quantity consumed) are important correlates of alcohol and drug use in sexual minority populations. The current study incorporates both of these by examining LGB individuals’ perceptions of peers’ use of alcohol and other drugs to cope with a sexual minority stressor, and whether perceptions of peer coping norms relate to one’s own coping-motivated substance use in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 20 publications
(24 reference statements)
0
37
0
Order By: Relevance
“…To this extent, a possible mechanism through which daily discrimination elevates risk for nicotine and substance use within day is by evoking feelings of shame and personal dissatisfaction—in addition to feelings of anger, anxiety, sadness, and depression (Hatzenbuehler et al, 2009; Swim et al, 2009)—which may result in using substances to manage these feelings. This pathway is supported by cross sectional and longitudinal findings linking discrimination to substance use directly and indirectly through the mediated path of psychological distress (Livingston, Christianson, & Cochran, 2016), and through coping motives for use (Kuerbis et al, 2017; Boyle, LaBrie, Costine, & Witkovic, 2017; Feinstein & Newcomb, 2016). This pathway is also consistent with Hatzenbuehler’s (2009) mediational model of health disparity, which postulates that the link between discrimination and substance use is mediated by cognitive and affective responses to discrimination, including negative self-schemas, positive substance use expectancies, and coping motives for use.…”
Section: Discussionmentioning
confidence: 86%
“…To this extent, a possible mechanism through which daily discrimination elevates risk for nicotine and substance use within day is by evoking feelings of shame and personal dissatisfaction—in addition to feelings of anger, anxiety, sadness, and depression (Hatzenbuehler et al, 2009; Swim et al, 2009)—which may result in using substances to manage these feelings. This pathway is supported by cross sectional and longitudinal findings linking discrimination to substance use directly and indirectly through the mediated path of psychological distress (Livingston, Christianson, & Cochran, 2016), and through coping motives for use (Kuerbis et al, 2017; Boyle, LaBrie, Costine, & Witkovic, 2017; Feinstein & Newcomb, 2016). This pathway is also consistent with Hatzenbuehler’s (2009) mediational model of health disparity, which postulates that the link between discrimination and substance use is mediated by cognitive and affective responses to discrimination, including negative self-schemas, positive substance use expectancies, and coping motives for use.…”
Section: Discussionmentioning
confidence: 86%
“…Another study found that sexual minority adult women perceived sexual minority women to drink more than heterosexual women and that more descriptive social norms (i.e., norms related to women in general and those specific to sexual minority women) and alcohol use were positively associated with each other over time (Litt et al, 2015). Moreover, a recent study found that sexual minority adults misperceived their sexual minority peers to be more likely to use alcohol and drugs to cope with minority stress (i.e., 2016 Orlando nightclub shooting), considering only a small portion of the sample was likely to do so (Boyle et al, 2017). These studies underscore the importance of examining social norms in understanding substance use; however, they did not clearly delineate between descriptive and injunctive norms, test the effects of norms on multiple substances, or examine these norms specifically among adolescents or with racially diverse samples.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual minority youth may experience rejection from their families of origin and peer groups while they are exploring and integrating their sexual orientation identities; friends therefore become an important source of support and influence on risky behaviors. Indeed, evidence suggests that peers may play a critical source of support and shape norms for sexual minority youth as a result of negativity from families and other social networks (Boyle et al, 2017). Sexual minority youth thus may be more willing to use substances if offered by a friend than their non-sexual minority counterparts as a function of a desire for peer acceptance and identity affirming group affiliations (Hatzenbeuhler, 2009; Dermody et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A small but emerging body of literature suggests that aspects of an individual’s social network may account for sexual orientation disparities in substance use behaviors (Hatzenbueler, McLaughlin, & Xuan, 2016; Boyle, LaBrie, Costine, & Witkovic, 2017). As a result of stigma from families and other peers and as a consequence of sexual orientation identity development, friends may be a particularly salient source of support for sexual minority youth (Gamarel, Walker, Rivera, Golub, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation